Digital Storytelling as an innovation to enhance college students’ speaking skills in English language - Kudaibergen, A.I.; Turebayeva, Sh.M. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2025)
Mastering the English language is vital in today’s globalized digital world, especially speaking skills for effective social interaction. While many feel they need more confidence in acquiring speaking skills, particularly in the speaking class, the results of this study highlight the unique benefits of integrating digital storytelling, which can serve as an effective approach to overcoming this difficulty. Consequently, learners are encouraged to present the stories in an engaging and entertaining way through the use of multimedia components such as images, music, and videos in new method of teaching. A quasi-experimental design was implemented, which included 62 students from the pedagogical college of Astana International University, comprising an experimental group and a control group. The experimental group employed digital storytelling tools, while the control group participated in conventional speaking practice. Pre-tests, post-tests, and questionnaires were administered before and after the teaching practice to examine whether any improvements were achieved in the speaking practice and the students’ views. Findings indicate the considerable progress made by the experimental group in the students’ speaking ability, which includes appropriate volume, logical progression of ideas, and the use of appropriate media elements. Qualitative feedback highlighted increased confidence, enhanced creativity, and improved pronunciation and fluency among students using digital storytelling. The results indicate that digital storytelling is a unique and effective method for enhancing speaking skills in the English language, offering valuable substance for teachers. Teachers can design more dynamic, engaging, and effective learning backgrounds by blending digital storytelling into language teaching.
Digital Storytelling колледж студенттерінің ағылшын тілінде сөйлеу дағдыларын жақсартуға арналған инновация ретінде
Digital Storytelling как инновация для улучшения разговорных навыков студентов колледжей на английском языке
Keywords: digital storytelling; innovation in education; technology in education; English language proficiency; speaking skills enhancement; student engagement; creative learning methods